The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1029/2004ja010545
|View full text |Cite
|
Sign up to set email alerts
|

Auroral particle acceleration by strong double layers: The upward current region

Abstract: [1] Satellite observations have established that parallel electric fields of both upward and downward current regions of the aurora are supported, at least in part, by strong double layers. The purpose of this article is to examine the role of double layers in auroral electron acceleration using direct measurements of parallel electric fields and the accompanying particle distributions, electrostatic waves, and nonlinear structures; the concentration is on the upward current region. Direct observations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
99
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 33 publications
15
99
1
Order By: Relevance
“…Likewise, Figures 15b and 15c show the ion distributions above and below the DL, reproduced from Figure 6 of Ergun et al [2004]. Above the DL both FAST and simulated data show upgoing ion beam.…”
Section: Electron and Ion Velocity Distribution Functionsmentioning
confidence: 81%
See 2 more Smart Citations
“…Likewise, Figures 15b and 15c show the ion distributions above and below the DL, reproduced from Figure 6 of Ergun et al [2004]. Above the DL both FAST and simulated data show upgoing ion beam.…”
Section: Electron and Ion Velocity Distribution Functionsmentioning
confidence: 81%
“…Figure 14a shows the electron velocity distribution functions above the DL in the height range 4100 < y/l d < 4800 (solid line) and below the DL for 1900 < y/l d < 2600 (dashed line). Figures 14b and 14c, reproduced from Figure 6 of Ergun et al [2004], are measured distributions above and below a DL, respectively. Note that in the FAST data positive (negative) velocities are downward (upward), exactly opposite to our simulations.…”
Section: Electron and Ion Velocity Distribution Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Mozer and Hull (2001) and more recently Ergun et al (2004) reported that auroral density cavities are the locations for large parallel electric fields (E || ), which are invariably accompanied with perpendicular electric fields (E ⊥ ) in the upward current region (UCR) of the auroral plasma. The ratio of E || to (E ⊥ ) ranges from ∼0.25 to O(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, this double layer only carries a small part of the total voltage. Ergun et al (2004) observed mid cavity double layers that held a small fraction of the potential drop in the presence of wave turbulence. It is thus likely that midcavity double layers are dynamic in nature.…”
Section: Conclusion and Discussionmentioning
confidence: 99%